PENGARUH TEH TOR BANGUN TERHADAP PENINGKATAN PRODUKSI ASI - Kristin - Natalia (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
Breastfeeding is a beautiful process and very beneficial, medical researchers have proven that breast milk has various advantages that are irreplaceable with any milk. Research objective: To determine the effect of the leaves of Bangun- Bangun on increasing breast milk production in breastfeeding mothers in Selayang Village, the working area of the Puskesmas Kesejahteraan, Prestasi District, Langkat Regency. The research methodology is using a Quasi Experiment Design research design using a Non-Equevalent Control Group approach. This study looked at how the effect of giving the leaves of wake-waking tea on milk production in nursing mothers with a total sample of 20 people. Univariate analysis was carried out using descriptive analysis to see the characteristics of each of the variables studied. The results of the analysis will be presented in the form of a frequency distribution. Bivariate analysis is the mean difference between the 2 groups that are treated and the control by looking at the influence between the two variables. In this study, the Independent T-test was conducted to measure the significance of the difference between the 2 groups.Research Results: The results of this study obtained a p value = 0.000 (p value <0.05) meaning that Ho was rejected, which means that there is an effect of wake-awara leaves on milk production in Sidodadi village, Delitua Health Center Work Area in 2023. Conclusion: It is hoped that institutions can facilitate research development by adding book sources and establishing collaboration with related agencies and future researchers are expected to be able to develop this research by using Bangun- Bangun leaves as herbal medicine to cure other diseases.